Intention to Extend Working Life among Thai Registered Nurses in Ministry of Public Health: A National Survey. (16th June 2019) - Sirisub, Pooncharat; Suwannapong, Nawarat; Tipayamongkholgul, Mathuros; Howteerakul, Nopporn; Noree, Thinakorn
Abstract : The serious shortage of registered nurses (RNs) in Thailand has made the Thai government tentatively propose a policy to extend the working life of Ministry of Public Health nurses. This study aimed to estimate the proportion of those RNs who intend to extend their working life and analyzed the associations between general characteristics, quality of work life, and job characteristics of the RNs and their intention to work past retirement age. This cross-sectional study was conducted from October 2016 to April 2017. Self-administered questionnaires were distributed nationally to 3, 629 RNs in the age group 55-59 years and working for the Ministry of Public Health (MoPH), Thailand. The response rate was 85.0% (3, 092 RNs). Due to the small number of male participants (n=74), males were excluded from the study. The analysis was limited to the 3, 018 participants who returned the questionnaire and met the inclusion criteria. Descriptive statistics and multiple logistic regression were used for data analysis. Of the 3, 018 participants, the proportion of RNs intending to extend their working life from 60 to 65 years was 30.5%. In the Service Department, the factors significantly associated with intention to extend working life were perceived good or very good health status, no shift work, monthly income more than 50, 000 THB (1, 595 USD), and having moderate or good working resources (p<0.01). In the four Academic Departments, perceived good or very good health status, monthly income more than 50, 000 THB, family members not against the working life extension, and moderate or good working resources were the factors affecting intention to extend working life (p<0.01). This study indicated that understanding the various factors related to the intention to extend working life among RNs could lead to the design of appropriate programs to encourage them to continue working after the current retirement age.